Aggregate Fiscal Impact of COVID-19 - World Bank (World Bank, Washington, DC, 2021)
This note analyzes the short-term effects of the COVID-19 (coronavirus) shock during the first year of the crisis and presents alternative medium-term recovery scenarios. It asks a set of questions, and in answering those questions, provides policy suggestions for the Vietnamese authorities'consideration. These questions are: (i) How were tax revenues affected by the shock, and how, in turn, did they affect the fiscal space available to the authorities What tax measures did the authorities implement to mitigate the shock and how successful were they What are the implications for any future tax policy and tax administration reforms (ii) How did the COVID-19 shock affect expenditures What fiscal measures did the authorities implement to mitigate the shocks, and how successful were they (iii) How did the shock affect fiscal balances and public debt (iv) What are the growth and fiscal prospects in the medium term